(untitled) - Konecny, Vladimir (Doprava a spoje, 2012)
Paper deals with commercial vehicle taxation in the Slovak republic. It includes comparison and differences between tax rates applied in concrete self-governing regions of the Slovak republic. Article also compares tax rates in European countries and defines recommendations in the field of vehicle taxation.